2008
DOI: 10.1111/j.1600-0447.2008.01164.x
|View full text |Cite
|
Sign up to set email alerts
|

The mental health impact of terrorism in Israel: A repeat cross‐sectional study of Arabs and Jews

Abstract: We suggest that certain conditions inherent to political conflict situations may potentially put minorities at risk and may only be observable as terrorism-related stressors become chronic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 70 publications
4
44
1
Order By: Relevance
“…It is possible, therefore, that older adults can adjust adequately to a single traumatic event or even to short term events (Böttche et al, 2012), while being more susceptible to long lasting exposure. Moreover, older individuals might find it more difficult to balance their resources during continuous stressful situations (Gelkopf et al, 2008;Hobfoll et al, 2006) due to lower social support or due to decreased flexibility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible, therefore, that older adults can adjust adequately to a single traumatic event or even to short term events (Böttche et al, 2012), while being more susceptible to long lasting exposure. Moreover, older individuals might find it more difficult to balance their resources during continuous stressful situations (Gelkopf et al, 2008;Hobfoll et al, 2006) due to lower social support or due to decreased flexibility.…”
Section: Discussionmentioning
confidence: 99%
“…Since 2001, the political violence and warfare between Israel and the Palestinians has caused many casualties and injuries on both sides, and has led to considerable psychological symptomatology among civilians (Gelkopf et al, 2008;Hobfoll et al, 2006). Moreover, the repeated attacks brought destruction of property and caused significant disturbance to daily life activities.…”
Section: Introductionmentioning
confidence: 99%
“…During this time, more than 13,000 attacks were carried out leaving over 1000 dead and nearly 6000 injured comprising roughly 0.1% of the population ("Ministry of Foreign Affairs," 2007). The death rate represents a population death rate over ten times the magnitude of the World Trade Center bombings (Gelkopf, Solomon, Berger, & Bleich, 2008). These attacks struck randomly and indiscriminately throughout the country, without prior warning.…”
Section: An Example Of Ongoing Terrorism: the Second Intifada In Israelmentioning
confidence: 99%
“…Another study, which compared Jews and Arabs exposed to acts of terror at two time points, found that at the first time point both groups reacted in a similar manner, but at the second time point the Arabs indicated higher levels of post-traumatic distress and lower levels of emotional strength than the Jews. The researchers concluded that political conflict is liable to place minority groups in danger of experiencing post-traumatic symptoms, yet these are more readily observed when they become chronic (Gelkopf, Solomon, Berger, & Bleich, 2008). Other comparative studies showed more symptoms of stress disorder in Arabs than in Jews, where a higher proportion of the former reported disassociation symptoms, feelings of re-experiencing the event, increased arousal, and symptoms of depression (Somer, Maguen, Or-Chen, & Litz, 2007;Yahav & Cohen, 2007).…”
Section: Post-traumatic Symptoms Among Israeli Arabsmentioning
confidence: 96%